A Photoisomerization‐Activated Intramolecular Charge‐Transfer Process for Broadband‐Tunable Single‐Mode Microlasers. (15th July 2020) - Qiao, Chan; Zhang, Chunhuan; Zhou, Zhonghao; Dong, Haiyun; Du, Yuxiang; Yao, Jiannian; Zhao, Yong Sheng
Abstract: Miniaturized lasers with high spectral purity and wide wavelength tunability are crucial for various photonic applications. Here we propose a strategy to realize broadband‐tunable single‐mode lasing based on a photoisomerization‐activated intramolecular charge‐transfer (ICT) process in coupled polymer microdisk cavities. The photoisomerizable molecules doped in the polymer microdisks can be quantitatively transformed into a kind of laser dye with strong ICT character by photoexcitation. The gain region was tailored over a wide range through the self‐modulation of the optically activated ICT isomers. Meanwhile, the resonant modes shifted with the photoisomerization because of a change in the effective refractive index of the polymer microdisk cavity. Based on the synergetic modulation of the optical gain and microcavity, we realized the broadband tuning of the single‐mode laser. These results offer a promising route to fabricate broadband‐tunable microlasers towards practical photonic integrations. Abstract : Gaining ground : Optical excitation of spiropyrans quantitatively transforms them into merocyanines with a strong intramolecular charge‐transfer (ICT) emission. The gain region of the merocyanine isomers shifted with photoisomerization because the increased polarity of the molecular environment lowered the ICT energy levels. Broadband‐tunable single‐mode lasing was achieved based on the controllable ICT processes in polymeric coupled microdisks.